Relations publiques - Violaine Appel; Hélène Boulanger; Alain Lavigne (Communication)
The concept of public relations has continuously evolved since its inception. We looked at the founding texts of public relations to understand how universities and professionals appropriate, model, and evolve the concept in line with societal changes and professional challenges. Then we examined the paradigm shift introduced and the new professional practices it spawned.